The impact of government procurement composition on private R&D activities - Viktor Slavtchev; Simon Wiederhold (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
This paper addresses the question of whether government procurement can work as a de facto innovation policy tool. We develop an endogenous growth model with quality-improving in-novation that incorporates industries with heterogeneous innovation sizes. Government de-mand in high-tech industries increases the market size in these industries and, with it, the in-centives for private firms to invest in R&D. At the economy-wide level, the additional R&D induced in high-tech industries outweighs the R&D foregone in all remaining industries. The implications of the model are empirically tested using a unique data set that includes federal procurement in U.S. states. We find evidence that a shift in the composition of government purchases toward high-tech industries indeed stimulates privately funded company R&D.
Keywords: E62; H54; H57; O31; O32; O41; 330; public demand; technological change; endogenous growth; Öffentliche Beschaffung; Hochtechnologiesektor; Innovationspolitik; Industrielle Forschung; USA